The Functional Analysis of the Presidential Institution in Albania - Jeha, Ilda (European Scientific Journal, ESJ, 2017)
The Constitution of the Republic of Albania lays down the functional duties of the President of the Republic. Although the functions may have changed along the years, the President of the Republic has many important duties for the smooth operation of things in the country. Obviously, the President’s Office is entrusted an unusual burdern that often puts it in a tight spot:on one side, quality of any decision issued is expected, but, on the other, the staff is quite limitted. These circumstances give particular importance to enhancing the efficiency of staff in this institution by optimising its organisational set-up; but, the approach imposed by the constitutional functions make it impossible for the President’s advisors to deliver the proper quality. On the contrary, all main and auxiliary functions need to be fulfilled by separate institutional units under the Secretary-General. Besides, the Assembly must immediately adopt an organic Law for the President, clearly stipulating how the President’s Office must act in line with each constitutional function. Such law would consolidate the President’s Office position against any spontanous reaction and would avert any controversies on how it acts, as it would legaly align procedures to actions.